2010
DOI: 10.1016/j.cub.2010.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Proper Organization of Microtubule Minus Ends Is Needed for Midzone Stability and Cytokinesis

Abstract: SUMMARY Successful cytokinesis is critical for maintaining genome stability [1, 2], and requires the assembly of a robust central spindle to specify the cleavage furrow position [3], to prevent separated chromosomes from coming back together [4], and to contribute to midbody abscission [5, 6]. A proper central spindle is assembled and maintained by a number of microtubule-associated and molecular motor proteins that sort microtubules into bundles with their plus-ends overlapping at the center [1, 2]. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Localizing on the mitotic spindle (Quintyne et al, 2005), KIFC1 manages spindle length both in mitosis and meiosis using its sliding activity along microtubules (Cai et al, 2009). In addition, KIFC1 mediates proper cytokinesis by organizing and stabilizing spindles (Cai et al, 2010). Depletion of KIFC1 induced multipolar spindle and genomic instability when large-scale analysis of human kinesin esiRNA library was performed in HeLa cells (Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Localizing on the mitotic spindle (Quintyne et al, 2005), KIFC1 manages spindle length both in mitosis and meiosis using its sliding activity along microtubules (Cai et al, 2009). In addition, KIFC1 mediates proper cytokinesis by organizing and stabilizing spindles (Cai et al, 2010). Depletion of KIFC1 induced multipolar spindle and genomic instability when large-scale analysis of human kinesin esiRNA library was performed in HeLa cells (Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be determined whether a stabilisation of interpolar microtubules that pre-exist from metaphase is sufficient for the formation of the central spindle or whether de novo microtubule polymerisation (Uehara and Goshima, 2010) is also required. The molecular details of the anchoring of the microtubule minus ends or their stabilisation without a specific anchoring structure are also unclear, although c-tubulin (Julian et al, 1993;Shu et al, 1995) and its associated proteins, such as augmin (Uehara et al, 2009) and minus-end-directed motor kinesin-14 (Cai et al, 2010), as well as the recently identified microtubule minus-end stabiliser patronin (Goodwin and Vale, 2010) have been suggested to be involved. By contrast, the roles of motors and microtubule-associated proteins (MAPs) that localise to the central anti-parallel overlaps have been better characterised as described below.…”
mentioning
confidence: 99%
“…S1D and F), indicating that it did not mimic KIFC1's activity in mediating congression of microtubules at the start of telophase. 3 However, once cells were established in telophase, KIFC3 transited to the minus-ends of the microtubules of the central bridge. We established this localization for endogenous and GFP/mCherry-tagged forms of KIFC3 in both HeLa ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…22 Pkl1 and HSET, by contrast, appeared to bind via microtubule-nucleating factors (γ-tubulin and augmin) that were associated with microtubule minus-ends. 3,6 To determine whether KIFC3 likewise tracked with moving microtubule ends, we examined mCherry-KIFC3 localization relative to growing microtubules in MDCK cells during the recovery from microtubule depolymerization by nocodazole. In these cells, microtubules are nucleated at the centrosome but released and captured elsewhere to give rise to the characteristic non-centrosomal microtubule organization of polarized epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation